A high temperature sinterable resin-based conductive composite material and preparation method thereof
By using single-walled carbon nanotubes in resin-based composite materials and predispersed by hyperbranched polymers, the problem of the conductive material degradation at high temperatures and after sintering is solved, and uniform dispersion and excellent conductive properties are achieved.
Patent Information
- Application Number
- CN202410892518.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-07-04
AI Technical Summary
The conductivity of existing conductive materials decreases at high temperatures and sintering, and it is difficult to achieve uniform dispersion in resin-based composite materials, affecting the mechanical properties and construction properties.
Single-walled carbon nanotubes are used as conductive material and pre-dispersed by hyperbranched polymers such as hyperbranched polyborate to form a mixture of single-walled carbon nanotubes to ensure that they are evenly dispersed in the resin-based composite material.
It achieves good and uniform conductivity at high temperatures and sintering, and improves the construction performance of composite materials and the mechanical properties after curing.
Smart Images

Figure CN118879021B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of conductive resins, and in particular to a high-temperature sinterable resin-based conductive composite material and a preparation method thereof. Background Art
[0002] High temperature sinterable resin materials and their preparation and application are essential material technology projects in the field of high temperature operations. For the bonding materials between two or more parts, that is, adhesives, or the outer protective materials of important parts, that is, coatings, these adhesives and coatings are sometimes required to have a certain conductivity to achieve the functions of conductivity, antistatic or electromagnetic shielding. Such resin matrices are often phenolic resins, epoxy resins or epoxy phenolic resins. These resins have excellent bonding ability with metals and ceramic materials. Hybrid resins containing silicon, boron and other elements can also be used to improve heat resistance. For sinterable composite materials, ceramic powders such as zinc oxide, magnesium oxide, aluminum nitride, boron nitride, kaolin, silicon carbide, etc. are usually added to the resin material. In order to make the resin material have a certain conductivity, conductive materials such as metals, carbon series or intrinsic conductive polymers are usually added to it to form a composite material.
[0003] For resin-based conductive composite materials, conductive fillers such as metals, carbon or intrinsic conductive polymers are usually added to resin materials to form composite materials. The composite materials have certain conductive properties after curing and when used at high temperatures.
[0004] However, the conductive materials currently used all have various defects: metal powders and conductive fibers need to be added in large quantities to achieve good conductivity, which also has a significant negative impact on the mechanical properties of the polymer; the microscopic lamellar structure and surface inertness of graphite powder make it difficult to be compatible and stably dispersed in uncured polymer composites, and also have a negative impact on the mechanical properties; after the conductive fibers are cured, the sheet-shaped or roll-shaped conductive composite materials make it inconvenient to adjust the conductive properties; conductive carbon black and multi-walled carbon nanotubes (MWCNTs) have an impact on processing and construction properties, and after sintering, their conductive properties will be significantly reduced.
[0005] At present, SWCNT, or single-walled carbon nanotube, is made of a single layer of graphene, and its manufacturing is difficult. SWCNT has an extremely small diameter (about 1-2nm) and an extremely high aspect ratio (about 3000:1), and due to the different preparation methods, SWCNT does not have the common agglomeration and entanglement problems of multi-walled carbon nanotubes, which makes single-walled carbon nanotubes have excellent electrical conductivity, so the addition amount is extremely low, and there is no negative impact on the construction performance of the composite material and the mechanical properties after curing. At the same time, single-walled carbon nanotubes also have excellent high temperature resistance due to the special structure, the use temperature can reach 1000℃, and the vacuum heat resistance temperature can reach 1600℃. Therefore, SWCNT is an ideal conductive filler for high-temperature sinterable resin-based composite materials. However, the high specific surface area of single-walled carbon nanotubes makes it difficult to achieve uniform dispersion of single-walled carbon nanotubes in resin-based composite materials in practice: the use of small molecule dispersants has good wetting properties, but the ability to prevent secondary agglomeration of fillers is poor; although the use of general polymer dispersants can prevent secondary agglomeration to a certain extent, the wetting ability for carbon-based fillers with large specific surface areas and inert surfaces is not ideal. Summary of the invention
[0006] Based on this, it is necessary to provide a high temperature resistant sinterable resin-based conductive composite material and a preparation method thereof.
[0007] In order to solve the above technical problems, the present invention provides a high-temperature resistant sinterable resin-based conductive composite material. The raw materials of the conductive composite material include a resin prepolymer and a single-walled carbon nanotube mixture. The single-walled carbon nanotube mixture includes 0.2-0.7 parts of single-walled carbon nanotubes, 0.15-0.25 parts of hyperbranched polymers and 5.65-11.25 parts of other additives in parts by weight. The single-walled carbon nanotube mixture is uniformly dispersed in the resin prepolymer through the hyperbranched polymer.
[0008] Preferably, the other auxiliary agents include 0.15-0.25 parts by weight of dimethyl sulfoxide, 4-8 parts by weight of ethyl acetate and 1.5-3 parts by weight of butyl acetate.
[0009] Preferably, the resin prepolymer is at least one of a phenolic resin prepolymer, an epoxy resin prepolymer or an epoxy phenolic resin prepolymer. When the resin prepolymer is a phenolic resin prepolymer, the phenolic resin prepolymer is a resorcinol-formaldehyde resin.
[0010] Preferably, the raw materials of the conductive composite material further include, by weight, 18-22 parts of butyl acetate, 90-110 parts of ethyl acetate, 3-20 parts of boron carbide powder, 3-20 parts of silicon carbide powder and 14-20 parts of hexamethylenetetramine.
[0011] Preferably, the preparation method of the single-walled carbon nanotube mixture comprises the following steps: mixing single-walled carbon nanotubes, hyperbranched polymers, dimethyl sulfoxide, ethyl acetate and butyl acetate, and dispersing for 50-80 minutes to obtain a semi-finished product slurry; adding ethyl acetate to the semi-finished product slurry for a second time, and stirring for 10-25 minutes; finally, dispersing and standing under a first condition, and then dispersing under a second condition to obtain a single-walled carbon nanotube mixture.
[0012] Preferably, the hyperbranched polymer is a hyperbranched polyborate, and the preparation method of the hyperbranched polyborate comprises the following steps: adding resorcinol to a solvent N-methylpyrrolidone, stirring and dissolving at 50-70°C to obtain a mixed solution, then filling nitrogen into a stirring kettle containing the mixed solution for protection, adding boric acid, and reacting at 150-170°C for 2.5-3.5 hours to obtain a hyperbranched polyborate.
[0013] Preferably, the present invention also provides a method for preparing the resin-based conductive composite material, comprising the following steps:
[0014] S1, adding resorcinol to N-methylpyrrolidone, stirring and dissolving at 50-70° C. to obtain a mixed solution, then filling nitrogen into a stirred tank containing the mixed solution for protection, adding boric acid, reacting at 150-170° C. for 2.5-3.5 hours, to prepare a hyperbranched polyborate, which is set aside;
[0015] S2, mixing single-walled carbon nanotubes, dimethyl sulfoxide, ethyl acetate, butyl acetate and the hyperbranched polyborate prepared in step S1, and dispersing for 50-80 minutes to obtain a semi-finished product slurry; adding ethyl acetate to the semi-finished product slurry for a second time, and stirring for 10-25 minutes; finally, dispersing and standing under the first condition, and then dispersing under the second condition to obtain a single-walled carbon nanotube mixture.
[0016] S3, mixing and stirring the resin prepolymer, butyl acetate and ethyl acetate until they are completely dissolved; then, adding the boron carbide powder, silicon carbide powder and the single-walled carbon nanotube mixture prepared in step S2, stirring for 30-50 minutes, adding hexamethylenetetramine and continuing to stir for 30-50 minutes to obtain an uncured resin composite, and vacuum drying to obtain a resin-based conductive composite material.
[0017] Preferably, in step S1, the molar ratio of resorcinol to boric acid is 5:2.
[0018] Preferably, in step S2, the weight ratio of the single-walled carbon nanotubes, hyperbranched polyborate, dimethyl sulfoxide, ethyl acetate and butyl acetate is 0.5:0.2:0.2:6.6:2.5.
[0019] Preferably, in step S3, the weight ratio of the resin prepolymer, the single-walled carbon nanotube mixture, butyl acetate, ethyl acetate, boron carbide powder, silicon carbide powder and hexamethylenetetramine is 100:10:20:100:5:7.5:16.
[0020] The beneficial effects of the present invention are as follows: the present invention synthesizes a hyperbranched polymer, then uses single-walled carbon nanotubes as a conductive material, and uses the hyperbranched polymer, namely, hyperbranched polyborate, as a dispersant for the single-walled carbon nanotubes to pre-disperse the single-walled carbon nanotubes to form a single-walled carbon nanotube mixture; in the preparation of a composite material based on a conductive phenolic resin, the single-walled carbon nanotubes are dispersed by a dispersant with a large molecular weight and good wetting performance, thereby avoiding many defects caused by using traditional conductive materials and improving the dispersion of the single-walled carbon nanotubes in the resin-based material; the composite material has excellent construction performance and bonding ability; and can show good and uniform conductive performance after being cured; and can still maintain good and uniform conductive performance under high temperature or after sintering. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the molecular structure of the hyperbranched polyborate in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0022] To facilitate understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings.
[0023] It should be noted that when an element is considered to be "connected" to another element, it may be directly connected to another element and integrated therewith, or there may be an intermediate element at the same time. The terms "installed", "one end", "the other end" and similar expressions used herein are for illustrative purposes only.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art. The terms used in the specification herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0025] The present invention provides a high temperature resistant sinterable resin-based conductive composite material, wherein the raw materials of the conductive composite material, by weight, include 90-110 parts of resin prepolymer and 6-12.2 parts of single-walled carbon nanotube mixture, wherein the single-walled carbon nanotube mixture includes 0.2-0.7 parts of single-walled carbon nanotube, 0.15-0.25 parts of hyperbranched polymer and 5.65-11.25 parts of other additives by weight, and the single-walled carbon nanotube mixture is uniformly dispersed in the resin prepolymer through the hyperbranched polymer. Hyperbranched polyborate is used as a dispersant for single-walled carbon nanotubes to pre-disperse them to form a single-walled carbon nanotube mixture; the dispersant of the present invention is a self-made hyperbranched polymer, which has good wetting properties and excellent ability to prevent secondary agglomeration of fillers, so that the single-walled carbon nanotubes are uniformly dispersed in the resin-based composite material, solving the problem that the conductive properties of the materials are affected due to uneven dispersion. The single-walled carbon nanotube mixture is a pre-dispersed slurry of single-walled carbon nanotubes obtained by an independent preparation method after being dispersed by hyperbranched polyborate.
[0026] In a preferred embodiment, the other auxiliary agents include 0.15-0.25 parts by weight of dimethyl sulfoxide, 4-8 parts by weight of ethyl acetate and 1.5-3 parts by weight of butyl acetate.
[0027] In a preferred embodiment, the resin prepolymer is at least one of a phenolic resin prepolymer, an epoxy resin prepolymer or an epoxy phenolic resin prepolymer. When the resin prepolymer is a phenolic resin prepolymer, the phenolic resin prepolymer is a resorcinol-formaldehyde resin.
[0028] In a preferred embodiment, the raw materials of the conductive composite material, by weight, further include 18-22 parts of butyl acetate, 90-110 parts of ethyl acetate, 3-20 parts of boron carbide powder, 3-20 parts of silicon carbide powder, and 14-20 parts of hexamethylenetetramine. Further, the raw materials of the conductive composite material, by weight, further include 18-22 parts of butyl acetate, 90-110 parts of ethyl acetate, 3-8 parts of boron carbide powder, 6-9 parts of silicon carbide powder, and 14-20 parts of hexamethylenetetramine.
[0029] In a preferred embodiment, the preparation method of the single-walled carbon nanotube mixture comprises the following steps: after mixing single-walled carbon nanotubes, hyperbranched polymers, dimethyl sulfoxide, ethyl acetate and butyl acetate, dispersing for 50-80 minutes to obtain a semi-finished product slurry; after adding ethyl acetate to the semi-finished product slurry for the second time, stirring for 10-25 minutes; finally, dispersing and standing under the first condition, and then dispersing under the second condition to obtain a single-walled carbon nanotube mixture. Preferably, the preparation method of the single-walled carbon nanotube mixture includes 0.45-0.6 parts of single-walled carbon nanotubes, 0.17-0.22 parts of hyperbranched polymers, 0.17-0.22 parts of dimethyl sulfoxide, 5.5-7.5 parts of ethyl acetate, and 2-3 parts of butyl acetate, based on the weight of the raw materials. Among them, the first condition is specifically: in a water bath condition with a temperature below 45°C, ultrasonically disperse for 200-350 seconds, and then stand for 24 hours; the second condition is specifically: in a water bath condition with a temperature below 45°C, ultrasonically disperse for 200-350 seconds.
[0030] Optionally, based on the weight of the raw materials, the mixture includes 0.2-0.7 parts of single-walled carbon nanotubes, 0.15-0.25 parts of hyperbranched polymers, 0.15-0.25 parts of dimethyl sulfoxide, 4-8 parts of ethyl acetate, and 1.5-3 parts of butyl acetate.
[0031] Optimally, the weight ratio of the single-walled carbon nanotube, hyperbranched polyborate, dimethyl sulfoxide, ethyl acetate and butyl acetate is 0.5:0.2:0.2:6.6:2.5.
[0032] In a preferred embodiment, the container is preferably a stirred tank, the hyperbranched polymer is a hyperbranched polyborate, and the preparation method of the hyperbranched polyborate comprises the following steps: N-methylpyrrolidone is placed in a stirred tank, resorcinol is added to the N-methylpyrrolidone, and a mixed solution is obtained after stirring and dissolving at 50-70°C, and then nitrogen is filled into the stirred tank containing the mixed solution for protection, so that the mixed solution is protected by nitrogen, boric acid is added, and the mixture is reacted at 150-170°C for 2.5-3.5 hours to obtain a hyperbranched polyborate.
[0033] In a preferred embodiment, the present invention further provides a method for preparing the resin-based conductive composite material, comprising the following steps:
[0034] S1, adding resorcinol to N-methylpyrrolidone, stirring and dissolving at 50-70° C. to obtain a mixed solution, then filling the mixed solution with nitrogen for protection, adding boric acid, reacting at 150-170° C. for 2.5-3.5 hours, to prepare a hyperbranched polyborate, which is set aside;
[0035] S2, after mixing single-walled carbon nanotubes, dimethyl sulfoxide, ethyl acetate, butyl acetate and the hyperbranched polyboric acid ester prepared in step S1, disperse the mixture for 50-80 minutes to obtain a semi-finished product slurry; add ethyl acetate to the semi-finished product slurry for the second time and stir for 10-25 minutes; finally, disperse and stand under the first condition, and then disperse under the second condition to obtain a single-walled carbon nanotube mixture. The first condition is specifically: in a water bath with a temperature below 45°C, ultrasonically disperse for 200-350 seconds, and then stand for 24 hours; the second condition is specifically: in a water bath with a temperature below 45°C, ultrasonically disperse for 200-350 seconds.
[0036] S3, the resin prepolymer, butyl acetate, ethyl acetate are mixed and stirred until completely dissolved; then, boron carbide powder, silicon carbide powder and the single-walled carbon nanotube mixture prepared in step S2 are added, stirred for 30-50 minutes, hexamethylenetetramine is added and stirred for 30-50 minutes to obtain an uncured resin composite, which is vacuum dried to obtain a resin-based conductive composite material. Specifically, vacuum drying includes vacuuming the uncured resin composite for 20-40 minutes, and then heating at 140-180°C for 40-80 minutes to obtain a finished resin-based conductive composite material.
[0037] In a preferred embodiment, in step S1, the molar ratio of resorcinol to boric acid is 5:2. The molar ratio of resorcinol to boric acid is 5:2, so that the prepared hyperbranched polyborate has excellent single-walled carbon nanotube dispersion performance, and the hyperbranched polyborate is used as a dispersant for single-walled carbon nanotubes to pre-disperse them to form a single-walled carbon nanotube mixture, and in the preparation of the conductive phenolic resin-based composite material, the single-walled carbon nanotubes are dispersed by a dispersant with a large molecular weight and good wetting properties.
[0038] In a preferred embodiment, in step S2, the weight ratio of the single-walled carbon nanotubes, hyperbranched polyborate, dimethyl sulfoxide, ethyl acetate and butyl acetate is: 0.2-0.7: 0.15-0.25: 0.15-0.25: 4-8: 1.5-3.
[0039] Furthermore, in step S2, the weight ratio of the single-walled carbon nanotubes, hyperbranched polyborate, dimethyl sulfoxide, ethyl acetate and butyl acetate is 0.5:0.2:0.2:6.6:2.5.
[0040] In a preferred embodiment, in step S3, the weight ratio of the resin prepolymer, the single-walled carbon nanotube mixture, butyl acetate, ethyl acetate, boron carbide powder, silicon carbide powder, and hexamethylenetetramine is: 90-110: 6-12.2: 18-22: 90-110: 3-20: 3-20: 14-20.
[0041] Furthermore, in step S3, the weight ratio of the resin prepolymer, the single-walled carbon nanotube mixture, butyl acetate, ethyl acetate, boron carbide powder, silicon carbide powder, and hexamethylenetetramine is 100:10:20:100:5:7.5:16.
[0042] In order to have a further understanding and recognition of the technical solution of the present invention, preferred embodiments are listed and further described in detail.
[0043] Example
[0044] Preparation of Hyperbranched Polyborates:
[0045] Resorcinol was added to N-methylpyrrolidone (NMP) solvent, and dissolved by stirring at 60°C; after N2 was charged for protection, boric acid was added, and the reaction was carried out at 160°C for 3 hours to obtain a hyperbranched polyborate; wherein the resorcinol and the boric acid were added in a molar ratio of 5:2.
[0046] Preparation of SWNTs mixture:
[0047] 0.5 parts by weight of single-walled carbon nanotubes, 0.2 parts by weight of hyperbranched polyborate, 0.2 parts by weight of dimethyl sulfoxide, 0.6 parts by weight of ethyl acetate, and 2.5 parts by weight of butyl acetate are added to a planetary disperser, and dispersed at medium-low speed for 60 minutes to obtain a semi-finished product slurry; the semi-finished product slurry is placed in a beaker and 6.0 parts by weight of ethyl acetate is added, and stirred at medium speed for 15 minutes with a desktop mixer; then, the beaker is placed in an ultrasonic disperser, at medium-low power, with a water temperature below 45°C, dispersed for 300 seconds, then allowed to stand for 24 hours, and then dispersed for 300 seconds under the same conditions to complete the preparation of the single-walled carbon nanotube mixture for use.
[0048] Preparation of resin-based conductive composite materials:
[0049] 100 parts by weight of resorcinol-formaldehyde resin, 20 parts by weight of butyl acetate and 100 parts by weight of ethyl acetate were added to a stirring kettle and mechanically stirred until completely dissolved. 0.5 parts by weight of the single-walled carbon nanotube mixture prepared in step S2, 5 parts by weight of boron carbide powder and 7.5 parts by weight of silicon carbide powder were added to the stirring kettle and stirred for 45 minutes, and then 16 parts by weight of hexamethylenetetramine were added and stirred for another 45 minutes to obtain an uncured resin composite.
[0050] The uncured resin composite prepared above was poured into a polytetrafluoroethylene mold and vacuumed for 30 minutes, and then the mold was placed in an oven and heated at 160° C. for 60 minutes to obtain a resin-based conductive composite sheet sample with a size of 15 mm×15 mm×3.0 mm.
[0051] Effect example
[0052] The conductive properties of the sheet samples with a size of 15 mm×15 mm×3.0 mm formed by the lipid-based conductive composite material prepared in the example under various conditions were compared and evaluated by resistance testing; the test process is as follows, and the test results are shown in Table 1.
[0053] Resistance test of resin-based conductive composite materials:
[0054] (1) First test: The upper and lower surfaces of the sheet sample were respectively adhered to the plate-shaped positive and negative electrodes of a resistance tester using a conductive double-sided tape. At room temperature, the resistance was measured to obtain a resistance value of 1.2 kΩ.
[0055] (2) Second test: Take the sheet sample and use a conductive double-sided tape to bond the upper and lower surfaces of the sheet sample to the plate-shaped positive and negative electrodes of the resistance tester, respectively. Preheat the oven so that the temperature inside the oven reaches 280°C. After the temperature stabilizes, place the sample and the electrodes bonded together in an oven at an internal temperature of 280°C for 5 minutes. Then test its resistance and obtain a resistance value of 8.5 kΩ.
[0056] (3) Third test: Place the above sheet sample in a crucible, place the crucible in a muffle furnace, introduce nitrogen gas for purging, heat to 1200°C, and maintain the temperature for 60 minutes, then cool naturally to room temperature to obtain a sintered sheet sample for later use; contact the needle electrode of the resistance tester with the surface of the sheet sample with an electrode spacing of 10 mm, measure 10 times at different positions of the sheet sample, and test its resistance to obtain a resistance value of 3.3 to 3.5 kΩ.
[0057] Table 1
[0058]
[0059]
[0060] As can be seen from the results shown in Table 1, it can be seen from the test results that after high temperature and sintering, the material of the present invention still has good electrical conductivity and resistance uniformity. According to the resin-based conductive composite material of the present invention, the dispersion of single-walled carbon nanotubes in the resin-based conductive composite material is improved by preparing a hyperbranched polymer with a large molecular weight and good wettability, avoiding the secondary agglomeration of single-walled carbon nanotubes, and improving the high-temperature sintering conductive performance of traditional resin-based conductive composite materials, so that after curing and high-temperature sintering, it still shows good and uniform conductive performance. At the same time, the resin-based conductive composite material of the present application has a reasonable formula, and the original resin-based conductive composite material has improved the poor dispersibility and poor heat resistance of the original resin-based conductive composite material by the hyperbranched polymer synthesized independently and the single-walled carbon nanotube mixture obtained by independent preparation.
[0061] In the third test, the needle electrode of the resistance tester is contacted with different points on the surface of the sheet sample, the distance between two adjacent points is 10 mm, and a total of 10 measurements are taken at different positions. The specific method of the 10 measurements is: one electrode is fixed at a fixed point on the sheet sample to be tested, and the other electrode selects 4 measurement points at different positions on the sheet sample to be tested. The resistance value obtained by the test resistance is in the range of 3.3 to 3.5 kΩ. The specific situation of the 10 measurements is shown in Table 2:
[0062] Table 2
[0063]
[0064]
[0065] From the results shown in Table 2, it can be seen that after high-temperature sintering, the resistance values measured at different points of the sheet sample are basically consistent, indicating that the single-walled carbon nanotubes are better dispersed in the resin-based conductive composite material, so that the conductive performance of the prepared material is uniform everywhere.
[0066] In this application, unless otherwise clearly specified and limited, in the description of this specification, the description of reference terms such as "preferred embodiment", "further embodiment", "other embodiments" or "specific example" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0067] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A high temperature sinterable resin-based conductive composite material, characterized in that: The raw materials of the conductive composite material include a resin prepolymer and a single-walled carbon nanotube mixture, wherein the single-walled carbon nanotube mixture includes, by weight, 0.2-0.7 parts of single-walled carbon nanotubes, 0.15-0.25 parts of hyperbranched polymers, and 5.65-11.25 parts of other additives, wherein the other additives include, by weight, 0.15-0.25 parts of dimethyl sulfoxide, 4-8 parts of ethyl acetate, and 1.5-3 parts of butyl acetate; the single-walled carbon nanotube mixture is uniformly dispersed in the resin prepolymer through the hyperbranched polymer; The resin prepolymer is at least one of a phenolic resin prepolymer, an epoxy resin prepolymer or an epoxy phenolic resin prepolymer. When the resin prepolymer is a phenolic resin prepolymer, the phenolic resin prepolymer is a resorcinol-formaldehyde resin. The preparation method of the single-walled carbon nanotube mixture comprises the following steps: mixing single-walled carbon nanotubes, hyperbranched polymers, dimethyl sulfoxide, ethyl acetate and butyl acetate, and dispersing for 50-80 minutes to obtain a semi-finished product slurry; adding ethyl acetate to the semi-finished product slurry for the second time, and stirring for 10-25 minutes; finally, dispersing and standing under a first condition, and then dispersing under a second condition to obtain a single-walled carbon nanotube mixture; the first condition is: in a water bath with a temperature below 45° C., ultrasonically dispersing for 200-350 seconds, and standing for 24 hours; the second condition is: in a water bath with a temperature below 45° C., ultrasonically dispersing for 200-350 seconds; The hyperbranched polymer is a hyperbranched polyborate.
2. The resin-based conductive composite material according to claim 1, characterized in that: The raw materials of the conductive composite material further include, by weight, 18-22 parts of butyl acetate, 90-110 parts of ethyl acetate, 3-20 parts of boron carbide powder, 3-20 parts of silicon carbide powder and 14-20 parts of hexamethylenetetramine.
3. The resin-based conductive composite material according to claim 1, characterized in that: The preparation method of the hyperbranched polyborate comprises the following steps: adding resorcinol into a solvent N-methylpyrrolidone, stirring and dissolving at 50-70° C. to obtain a mixed solution, then filling nitrogen into a container containing the mixed solution for protection, adding boric acid, and reacting at 150-170° C. for 2.5-3.5 hours to obtain the hyperbranched polyborate.
4. The method for preparing the resin-based conductive composite material according to any one of claims 1 to 2, characterized in that: The steps include: S1, adding resorcinol to N-methylpyrrolidone, stirring and dissolving at 50-70° C. to obtain a mixed solution, then filling nitrogen into a container containing the mixed solution for protection, adding boric acid, reacting at 150-170° C. for 2.5-3.5 hours, preparing a hyperbranched polyborate, and setting aside; S2, mixing single-walled carbon nanotubes, dimethyl sulfoxide, ethyl acetate, butyl acetate and the hyperbranched polyborate prepared in step S1, and dispersing for 50-80 minutes to obtain a semi-finished product slurry; adding ethyl acetate to the semi-finished product slurry for a second time, and stirring for 10-25 minutes; finally, dispersing and standing under the first condition, and then dispersing under the second condition to obtain a single-walled carbon nanotube mixture; S3, mixing and stirring the resin prepolymer, butyl acetate and ethyl acetate until they are completely dissolved; then, adding the boron carbide powder, silicon carbide powder and the single-walled carbon nanotube mixture prepared in step S2, stirring for 30-50 minutes, adding hexamethylenetetramine and continuing to stir for 30-50 minutes to obtain an uncured resin composite, and vacuum drying to obtain a resin-based conductive composite material.
5. The method for preparing the resin-based conductive composite material according to claim 4, characterized in that: In step S1, the molar ratio of resorcinol to boric acid is 5:
2.
6. The method for preparing the resin-based conductive composite material according to claim 4, characterized in that: In step S2, the weight ratio of the single-walled carbon nanotubes, hyperbranched polyborate, dimethyl sulfoxide, ethyl acetate and butyl acetate is: 0.5:0.2:0.2:6.6:2.5。 7. The method for preparing the resin-based conductive composite material according to claim 4, characterized in that: In step S3, the weight ratio of the resin prepolymer, the single-walled carbon nanotube mixture, butyl acetate, ethyl acetate, boron carbide powder, silicon carbide powder, and hexamethylenetetramine is 100:10:20:100:5:7.5:16.
Citation Information
Patent Citations
Electric-insulation heat-conduction epoxy resin composite material and preparation method thereof
CN101914264A
Carbon nanotube / benzoxazine / bimaleimide composite material and preparation method thereof
CN102796374A